Numerical construction of piecewise virtual fields - Syed Muhammad, Kashif (IIUM Press, 2011)
This chapter discusses the numerical issues in construction of piecewise virtual fields over a specimen. The improvement and advantages over the use of single virtual element has been examined. Such a piecewise construction has been successfully used to characterize a thin composite plate in bending. Moreover, the use of piecewise elements has shown its merits in the characterization of a damaged composite plate. An illustrated detailed discussion is presented on the choice of element that ensures continuity at the edges of adjacent elements and its importance.